Réponses

Meilleure réponse !
2014-05-10T12:04:38+02:00
Salut
1) (x+1)(x+1)
= x*2+2x+1
Donc, (x+1)*2=x*2+2x+1

2) (x-1)(x-1)
= x*2-2x+1
Donc, (x-1)*2= x*2-2x+1

3) (x+4)*2
= x*2+8x+16

(x-3)*2
= x*2-6x+9
Voila j'espère que je t'ai aidé
c'est toi qui est trop chou ;-)
:$ :D Thanks
derien :p
:))))) :DDD
<3
  • Utilisateur Brainly
2014-05-10T12:09:24+02:00
Bonjour, 

Ex 86 :

(x+1)(x+1) \\ =x^2+x+x+1 \\ =x^2+2x+1

Donc (x+1)^2=x^2+2x+1

(x-1)(x-1) \\ =x^2-x-x+1 \\ =x^2-2x+1

Donc (x-1)^2=x^2-2x+1

(x+4)^2 \\ =x^2+8x+16

(x-3)^2 \\ =x^2-6x+9

Bonne journée! =)